Acid-base chemistry of plasma: consolidation of the traditional and modern approaches from a mathematical and clinical perspective - Matousek, S; Handy, J; Rees, S E (Journal of clinical monitoring and computing, 2011)
OBJECTIVE: Debate still exists as to whether the Stewart (modern) or traditional model of acid-base chemistry is best in assessing the acid-base status of critically ill patients. Recent studies have compared various parameters from the modern and traditional approaches, assessing the clinical usefulness of parameters such as base excess, anion gap, corrected anion gap, strong ion difference and strong ion gap. To compare the clinical usefulness of these parameters, and hence the different approaches, requires a clear understanding of their meaning; a task only possible through understanding the mathematical basis of the approaches. The objective of this paper is to provide this understanding, limiting the mathematics to a necessary minimum. METHOD: The first part of this paper compares the mathematics of these approaches, with the second part illustrating the clinical usefulness of the approaches using a patient example. RESULTS: This analysis illustrates the almost interchangeable nature of the equations and that the same clinical conclusions can be drawn regardless of the approach adopted. CONCLUSIONS: Although different in their concepts, the traditional and modern approaches based on mathematical models can be seen as complementary giving, in principle, the same information about the acid-base status of plasma.
Keywords: teoretické modely; monitorování fyziologických funkcí; Monitoring, Physiologic; poruchy acidobazické rovnováhy; software; lidé; krevní plazma; Buffers; Acid-Base Imbalance; Algorithms; Plasma; Bicarbonates; Acid-Base Equilibrium; algoritmy; ionty; Software; Ions; acidobazická rovnováha; pufry; hydrogenuhličitany; Models, Theoretical; Humans